
Example: Simplify, log (36/25) + log (1225/36)  log (98/4). Solution: log (36/25) = log 36  log 25 = log 6^{2}  log 5^{2} = 2log 6  2log 5. log (1225/36) = log 1225  log 36 = log (5^{2}.7^{2})  log 6^{2} = 2log 5 + 2log 7  2log 6. log (98/4) = log 98  log 4 = log (7^{2}.2)  log 2^{2} = 2log 7 + log 2  2log 2 = 2log 7 + log 2 Therefore, log (36/25) + log (1225/36)  log (98/4) = [2log 6  2log 5] + [2log 5 + 2log 7  2log 6]  [2log 7 + log 2] = 2log 6  2log 5 + 2log 5 + 2log 7  2log 6  2log 7  log 2 = log 2 Directions: Solve the following problems. Also write at least ten examples of your own. 